Dual isotopic values and elemental concentrations (C & N) determined in muscle tissue of farmed (F) and wild (W) Totoaba macdonaldi - Gamboa Delgado, Julián; Sánchez Díaz, Ricardo (2024)
Supplementary data for article: Gamboa-Delgado, J. & Sánchez-Diáz, R. (2024). Wild or farmed: Carbon and nitrogen stable isotope values as natural biomarkers to improve the traceability of endangered totoaba (Totoaba macdonaldi, Sciaenidae). Aquatic Conservation: Marine and Freshwater Ecosystems. In press.